EFEKTIVITAS PETA STRATEGI DALAM ALOKASI BIAYA: SUATU EKSPERIMEN BERBASIS INTERNET - Handoko, Jesica; Narsa, I Made; Basuki, Basuki (Jurnal Akuntansi Kontemporer, 2022)
Research Purposes. This study aims to test whether there are differences in resource cost allocations when decision makers receive negative or positive information.Research Methods. This research with a 2x3x2 mixed subject design was conducted using an internet-based experimental application with the final result of 132 participants who passed the manipulation check.Research Results and Findings. The study results do not show differences in resource cost allocations when there are differences in performance achievement. The effectiveness of the strategy map is proven to be significant when the decision makers get the strategy map visualization, that is, there is no excessive allocation compared to those in the group without the strategy map visualization.